Knowing Bass: Accounting for Information Environments in Designing Online Public Outreach. Issue 2 (18th December 2018) - Pigg, Stacey; Reading, Benjamin J.
Social media and online news sites have become common outlets through which publics encounter information that shape their knowledge, values, and opinions about food. This article extends scholarship at the intersections of user experience design and online public outreach by focusing on the role of social media and online news sites in information environments that impact public site users' knowledge about and practices of seafood production and consumption. First, we introduce an ongoing design project about North Carolina seafood production and consumption to provide an example of how and why site designers should account for how online information affects public understanding. Next, we contextualize the challenges of this project by introducing a conceptual framework that helps to explain why the values and practices of understanding seafood production are so complex. Finally, through this case and framework, we argue that designers of online public outreach projects should become more aware of designing in contexts shaped by social media. The potential for public learning is affected by how people search for, encounter, and discuss information about the issues that matter to their lives. We offer a classroom heuristic for identifying and addressing the role of information environments in rhetoric and/or technical communication courses.